Role of the sharing economy in the achievement of energy efficiency and sustainable economic development: Evidence from China - Hongmei Jin; Hui Li; Tengbiao Zhao; Yu Pang (Journal of Innovation & Knowledge (JIK), 2023)
Globally, the sharing economy is considered a significant factor in achieving energy efficiency and sustainable economic development (SED) which needs regulatory and academic focus. This article investigates the impact of the sharing economy, including sharing economy users and sharing economy values, on efficient energy use and SED in China. The research uses exports, population growth, and foreign direct investment (FDI) as control variables. The article uses secondary data extracted from Statista, the sustainable development solution network, and World Development Indicators (WDI), from 1986 to 2020. The research applies the nonlinear autoregressive distributed lagged (NARDL) model to examine the associations among the variables. The results reveal that sharing economy users, sharing economy values, exports, population growth, and FDI have a positive association with efficient energy use and SED in China. This article guides policymakers establishing policies related to the achievement of SED and energy efficiency using the sharing economy. Governments, in particular, are recommended to actively encourage the growth of the sharing economy and create governance structures that support this growth.
Keywords: L86; Q01; Q49; 650; Energy efficiency; Exports; Population growth; Sharing economy; Sustainable economic development